2021
DOI: 10.1186/s12199-020-00929-7
|View full text |Cite
|
Sign up to set email alerts
|

The mechanism of enriched environment repairing the learning and memory impairment in offspring of prenatal stress by regulating the expression of activity-regulated cytoskeletal-associated and insulin-like growth factor-2 in hippocampus

Abstract: Background Prenatal stress can cause neurobiological and behavioral defects in offspring; environmental factors play a crucial role in regulating the development of brain and behavioral; this study was designed to test and verify whether an enriched environment can repair learning and memory impairment in offspring rats induced by prenatal stress and to explore its mechanism involving the expression of insulin-like growth factor-2 (IGF-2) and activity-regulated cytoskeletal-associated protein (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
15
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(20 citation statements)
references
References 50 publications
3
15
1
1
Order By: Relevance
“…The benefits of EE could be attributed to enhanced cerebral cortex thickness and synaptic arborization, enhanced serotonergic transmission in the frontal lobe, elevated levels of brain‐derived neurotrophic factor (BDNF), and increased hippocampal size (Leger et al, 2015). Contrasting with our results, Liu et al found improved memory from EE intervention in prenatally stressed rats that they attributed to hippocampal expression of activity‐regulated cytoskeletal‐associated protein (Arc) and insulin‐like growth factor‐2 (IGF‐2) (Guan et al, 2021). This could be explained by vastly differing methodology and different types of prenatal stress evaluated.…”
Section: Discussioncontrasting
confidence: 99%
“…The benefits of EE could be attributed to enhanced cerebral cortex thickness and synaptic arborization, enhanced serotonergic transmission in the frontal lobe, elevated levels of brain‐derived neurotrophic factor (BDNF), and increased hippocampal size (Leger et al, 2015). Contrasting with our results, Liu et al found improved memory from EE intervention in prenatally stressed rats that they attributed to hippocampal expression of activity‐regulated cytoskeletal‐associated protein (Arc) and insulin‐like growth factor‐2 (IGF‐2) (Guan et al, 2021). This could be explained by vastly differing methodology and different types of prenatal stress evaluated.…”
Section: Discussioncontrasting
confidence: 99%
“…This is likely caused by effects of EE on neuroplastic responses to injury. The finding that an EE can reduce the cognition impairment of SAE is in accord with similar observations in animals with other forms of brain dysfunction [43][44][45][46][47][48]. Healthy environments also afford similar benefits to humans.…”
Section: Discussionsupporting
confidence: 82%
“…Microglia-derived IGF-2 can also prevent TNF α -induced death of mature oligodendrocytes in vitro [ 88 ]. EE can increase the mRNA and protein expression levels of hippocampal IGF-2 in the offspring of prenatal chronically stressed rats [ 89 ]. Microglia express activin-A in demyelinating diseases, which is necessary for myelination after development and injury.…”
Section: Effect Of Enriched Environment On Myelinationmentioning
confidence: 99%